Building Canvas Strategy for Integrated Tourism Area and Benchmark: Blue Ocean Strategy Approach - Utami, Christina Whidya; Susanto, Hendro; Septina, Fanny; Pujirahayu, Yoseva Maria; Razak, Muhammad Nurdin (International Business Management - Universitas Ciputra, 2021)
This research aims to identify tourism factors that should be eliminate, reduce, raise, and create (ERRC) to indicate the characteristics of Blue Ocean Strategy (BOS) in order to revitalize the development of Kenjeran tourism area, Surabaya by taking into account aspects of education, local economic improvement, and environmental conservation. The research methodology is based on descriptive approach through analyzing the strength, weakness, opportunities, and threats (SWOT) to find the key success factor, the industry benchmarks, and the tourism market agents in order to understand the ERRC and to set a canvas strategy. The result shows that Revitalization is done by; Eliminating Aspect of Sustainable Environment including environmental pollution, abrasion, and unregulated zone. Reducing Aspect of Attractions, including: a shift in local culture and focus on shopping area. Factors that should be raise is Aspect of Accessibility and Empowerment, including: tourism facilities, and community capacity development. whereasWhereas elements that should be created are included in Aspect of Tourism Industry, including pattern of partnership and community development. The novelties of this research is using Blue Ocean Strategy via a 4-step approach: Eliminate, Reduce, Raise, and Create (ERRC) to revitalize an integrated tourist area. Keywords: Eliminate; Reduce; Raise and Create (ERRC); canvas strategy; Blue Ocean Strategy.